Flemish soils contain rhizobia partners for Northwestern Europe‐adapted soybean cultivars. (25th February 2022) - Van Dingenen, Judith; Garcia Mendez, Sonia; Beirinckx, Stien; Vlaminck, Lena; De Keyser, Annick; Stuer, Naomi; Verschaete, Severine; Clarysse, Alexander; Pannecoucque, Joke; Rombauts, Stephane; Roldan‐Ruiz, Isabel; Willems, Anne; et al.
Summary: In Europe, soybean ( Glycine max ) used for food and feed has to be imported, causing negative socioeconomic and environmental impacts. To increase the local production, breeding generated varieties that grow in colder climates, but the yield using the commercial inoculants is not satisfactory in Belgium because of variable nodulation efficiencies. To look for indigenous nodulating strains possibly adapted to the local environment, we initiated a nodulation trap by growing early‐maturing cultivars under natural and greenhouse conditions in 107 garden soils in Flanders. Nodules occurred in 18 and 21 soils in the garden and greenhouse experiments respectively. By combining 16S rRNA PCR on single isolates with HiSeq 16S metabarcoding on nodules, we found a large bacterial richness and diversity from different soils. Furthermore, using Oxford Nanopore Technologies sequencing of DNA from one nodule, we retrieved the entire genome of a Bradyrhizobium species, not previously isolated, but profusely present in that nodule. These data highlight the need of combining diverse identification techniques to capture the true nodule rhizobial community. Eight selected rhizobial isolates were subdivided by whole‐genome analysis in three genera containing six genetically distinct species that, except for two, aligned with known type strains and were all able to nodulate soybean in the laboratory.